2015
DOI: 10.5098/fhp.6.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Working Fluid, Filling Ratio and Number of Turns on Pulsating Heat Pipe Thermal Performance

Abstract: Pulsating heat pipe's (PHP) are one of the alternatives to conventional heat transfer technologies. First part of this paper, titled: thermohydrodynamic behavior of methanol charged closed loop pulsating heat pipe has given information about thermo-hydrodynamic operational characteristics such as; bubble nucleation and collapse, bubble agglomeration and pumping action, flow regime changes, pressure/temperature perturbations, dynamic instabilities, meta-stable non-equilibrium conditions etc. in the PHP. Present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In contrast to this, as shown above, no dryout phenomena were observed on the PHP with 1 × 1 mm 2 channels. The higher stability of PHP activity in the small-channel PHP for high heat powers is in good agreement with previous reports in the literature [10,14], as outlined in Section 2.1. For horizontal orientation, taking care to ensure a high PHP activity (bubble growth, collapse, fluid exchange between evaporator and condenser, etc.)…”
Section: 22supporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to this, as shown above, no dryout phenomena were observed on the PHP with 1 × 1 mm 2 channels. The higher stability of PHP activity in the small-channel PHP for high heat powers is in good agreement with previous reports in the literature [10,14], as outlined in Section 2.1. For horizontal orientation, taking care to ensure a high PHP activity (bubble growth, collapse, fluid exchange between evaporator and condenser, etc.)…”
Section: 22supporting
confidence: 92%
“…The reason is that as the number of channels increases, so does the internal pertubation in terms of bubble growth and collapse [10], which is one of the basic processes governing PHP activity and performance. Additionally, the higher level of local perturbations helps to avoid vapor phase recoiling in the evaporator and liquid merging in the condenser [14]. From this, it can be concluded that PHPs with a larger number of channels are likely to work in a more "stable" way, as the pulsating motion can be sustained for a larger range of input powers.…”
Section: Structure Of Examined Phpsmentioning
confidence: 96%
“…The dimensionless numbers depend on thermophysical properties of the WFs, which in turn depend on temperature. Temperature data reported in the literature are very limited [41][42][43][44][45][46][47][48]. Hence, the subsequent development of correlation is carried out with a total of 920 data.…”
Section: Prediction Model Using Rcamentioning
confidence: 99%
“…As the number of channels increases, so does the internal perturbation in terms of bubble growth and collapse [10], which is one of the basic processes governing PHP activity and performance. Additionally, the higher level of local perturbations helps to avoid vapor phase recoiling in the evaporator and liquid merging in the condenser [12]. From this, it can be concluded that PHPs with a large number of channels are likely to work more "stable" as the pulsating motion can be sustained for a larger range of input powers.…”
Section: Design Of Phpsmentioning
confidence: 97%